The Bergen 4-Day Treatment for Obsessive-Compulsive Disorder: Does It Work in a New Clinical Setting? - Launes, Gunvor; Laukvik, Inger Lill; Sunde, Tor; Klovning, Ingrid; Hagen, Kristen; Solem, Stian; Öst, Lars-Göran; Hansen, Bjarne; Kvale, Gerd (Frontiers in Psychology, 2019)
Sørlandet Hospital in Norway has a history of offering patients with obsessive-compulsive disorder (OCD) cognitive behavior group therapy using 12 weekly sessions of 2.5 hours each. A previous evaluation of this treatment has shown that 51.9% did not respond at post-treatment. Recently, a highly concentrated group-treatment format, the Bergen 4-day treatment (B4DT), has been shown to help more than 90% of patients with OCD post-treatment. Based on these positive results, it was decided to explore whether the B4DT could be a feasible format for delivering ERP at another clinic. Thirty-five consecutively recruited patients were included in the current pilot study, and assessed at pre-treatment, post-treatment, and 3-month follow-up. Treatment response rate (35% reduction in OCD-symptom score) was 94% at post-treatment, and 80% at follow-up. Seventy-four percent were in remission at post-treatment and 68% at follow-up. Only one patient dropped out of treatment. The patients were highly satisfied with the treatment content and format. The results indicate that the 4-day treatment could successfully be implemented at a new clinic.